Chromosome-scale genome assembly of Codonopsis pilosula and comparative genomic analyses shed light on its genome evolution - Chen, Bao-Zheng; Yang, Zi-Jiang; Yang, Ling; Zhu, Yi-Fan; Li, Xu-Zhen; Wang, Lei; Zhou, Ye-Peng; Zhang, Guang-Hui; Li, Da-Wei; Dong, Yang; Duan, Sheng-Chang (Frontiers in Plant Science, 2024)
Codonopsis pilosula, renowned for its edibility and medicinal properties, is a significant plant in traditional Chinese medicine. However, the lack of available genomic resources has hindered further research. This study presents the first chromosome-scale genome assembly of C. pilosula using PacBio CLR reads and Hi-C scaffolding technology. The assembly resulted in a high-quality genome of 679.20 Mb. The genome was anchored to 8 pseudo-chromosomes, with an anchoring rate of 96.5% and a scaffold N50 of 80.50 Mb. The completeness of assembly was determined to be 97.6% by using Benchmarking with Universal Single-Copy Orthologs (BUSCO). Notably, repetitive elements constituted 76.8% of the genome, with long terminal repeat retrotransposons (LTR-RTs) dominating this group of elements ( 39.17% of the genome). Using Ks analysis and syntenic depth analysis, the polyploidization history of three platycodonoid clade species was found to involve only the γ-WGT event. The ancestral karyotype of three platycodonoid clade species was identified as having 9 protochromosomes through karyotype evolutionary analysis. Moreover, non-WGD genes contributing to gene family expansion have been shown to have a positive impact, especially those arising from tandem duplications. These insights are crucial for understanding the genetic diversity and evolutionary biology of C. pilosula, contributing to its conservation and sustainable use.